Comparative Diagnostic Performance of Three Radiological Procedures for the Detection of Lumbar Disk Herniation - Kardaun, J. W. P. F.; Kardaun, O. J. W. F. (Methods of Information in Medicine, 1990)
Literature data on the diagnostic performance of phlebography, myelography, and CT scan applied to patients with suspected lumbar disk herniation (LDH) are analyzed to extract maximal information about their relative discriminatory power. Seventeen papers meeting the selection criteria contain 13 reports on myelography, 6 on phlebography, and 5 on CT. Sensitivity and specificity are considered simultaneously in logistic ROC space. The reports of each procedure are effectively summarized by a linear regression in logistic ROC space. Taking into account the individual confidence regions of sensitivity and specificity obtained from each report, the slope of the regression line is estimated by Generalized Least Squares (ML). This approach also allows to test the assumption of a common odds ratio (i.e., of a unit slope). The simply to determine common odds ratio as well as the perpendicular distance between the origin and the regression line (as a good approximation to the area under the ROC curve) are used as a measure for the discriminatory power of the procedures. For CT, homogeneity of sensitivity turns out to be much more likely than a common odds ratio. Based on the available, retrospective data, phlebography appears to have the highest performance in visualizing an LDH, followed by myelography and CT.
Keywords: Lumbar Disk Herniation; Myelography; Phlebography; CT; ROC analysis; Diagnostic Test Evaluation